2020
DOI: 10.3389/fvets.2020.606415
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase and Direct-Fed Microbials (DFM) Potential for Improvement of Live Performance, Energy Digestibility, and Reduction of Environmental Microbial Load of Broilers

Abstract: The challenge of identifying alternatives to subtherapeutic levels of antibiotic growth promoters (AGP) in animal feed has led to increased interest in feed additives such as exogenous enzymes and direct-fed microbials (DFM). Six corn soy-based dietary treatments were designed to investigate the effect of high-efficiency xylanase alone, Bacillus spp. probiotics alone, and their combination vs. a commonly used antibiotic growth promoter (bacitracin methylene disalicylate; BMD) on live performance and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Saleh et al ( 25 ) reported that feeding low energy diet (90 kcal/kg) reduced BWG, while adding xylanase increased BWG and improved FCR. Similar results were also reported by Nusairat and Wang ( 17 ) in broilers. Furthermore, Ravn et al ( 26 ) showed that the addition of a xylanase and arabinofuranosidase combination improved duodenum villi length; an indicator of enhanced growth performance of the broilers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Saleh et al ( 25 ) reported that feeding low energy diet (90 kcal/kg) reduced BWG, while adding xylanase increased BWG and improved FCR. Similar results were also reported by Nusairat and Wang ( 17 ) in broilers. Furthermore, Ravn et al ( 26 ) showed that the addition of a xylanase and arabinofuranosidase combination improved duodenum villi length; an indicator of enhanced growth performance of the broilers.…”
Section: Resultssupporting
confidence: 91%
“…The GH11 xylanases usually have a larger active site, and they are more substrate specific ( 14 ), and degradation produces short-chained oligosaccharide subunits that act as prebiotics for the beneficial bacteria in the gut ( 15 ). It has been shown that adding xylanase to poultry diets improves nutrient utilization by increasing its digestibility as well as alleviating the negative effect of many anti-nutritional compounds that the animal cannot digest ( 16 , 17 ). Furthermore, xylanase has been shown to have a protective effect on the intestinal mucosa barrier to alleviate the negative effect of Clostridium perfringens infection in 21 d old broilers ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the current results, DFMs have be reported to have the ability to improve AME in nutrient deficient diets ( Weallands et al, 2017 ; Nusairat and Wang, 2020 ). Again, this AME comparison may be less valuable as it adds additional factors such as fermentation and increased retention time to consider.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, α-amylase had a positive effect on feed conversion 59 . These enzymes increase the release of trapped nutrients, increasing energy utilization and reducing the cost of production 61 . Therefore, the production of the enzyme cocktail containing xylanase and α-amylase is advantageous for improving the poultry industry.…”
Section: Discussionmentioning
confidence: 99%